2012
DOI: 10.1002/app.38495
|View full text |Cite
|
Sign up to set email alerts
|

Role of crystalline ethylene‐propylene copolymer on mechanical properties of impact polypropylene copolymer

Abstract: Impact polypropylene copolymer (IPC) has been known as a multiphase material in which an ethylene-propylene (EP) random copolymer, serves as toughening component, is dispersed in the homo-polypropylene hPP matrix. The crystalline EP copolymer (cEP) is another component whose role and microstructural effect on the IPC properties has not been well understood. This work reveals the relationship between the microstructure of cEP and the mechanical properties, that is, impact and tensile resistance, of IPC. We clar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 22 publications
2
46
0
Order By: Relevance
“…We have shown that, under uniaxial stretching, the long propylene‐segment of the cEP delays the debonding of the EPR droplets and hPP matrix. Consequently it extends the breaking of the IPC specimen at higher strain . Tian et al .…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…We have shown that, under uniaxial stretching, the long propylene‐segment of the cEP delays the debonding of the EPR droplets and hPP matrix. Consequently it extends the breaking of the IPC specimen at higher strain . Tian et al .…”
Section: Introductionsupporting
confidence: 82%
“…Apart from neat commercial IPC, blended IPCs in various compositions were studied. The IPC components, i.e., hPP, EPR, and cEP, were separated from the neat IPC by solvent extraction method as reported previously . Three blended IPCs were prepared by blending the components in Xylene (1.0% wt) with added BHT at 130 °C in vial for 15 min before SAXS measurements.…”
Section: Methodsmentioning
confidence: 99%
“…The toughening mechanism is realized when the EPR particles blunt the crack and inhibit crack propagation [7]. This blended polypropylene is widely known as impact polypropylene (IPP) [7][8] [9][10]. and Wafai et al [23].…”
Section: Introductionmentioning
confidence: 99%
“…Based on short‐chain‐branch (SCB) frequency measured by GPC‐IR instrument, Rungswang et al . have made a similar assignment of these two peaks in C7‐sol fraction . By deconvoluting the MWD curve into multiple Schulz–Flory “most‐probable” distributions and adequately assigning the Flory components to the mi‐PP or s‐EP parts, molecular weight of the two parts have been estimated and summarized in Table .…”
Section: Resultsmentioning
confidence: 99%